UJI PUPUK KANDANG KOTORAN AYAM DAN PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI HITAM (Oryza sativa L. Var. Cempo Ireng) - Nur Khamidah; Siswadi Siswadi; Dewi Ratna Nurhayati (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on chicken manure manure and paclobutrazol test on rice plant growth and yield has been conducted in April - August 2020, located in Dibal Village, Ngemplak District, Boyolali Regency with a height of 150 meters above sea level with grumusol soil type. This research aims: to find out the effect of chicken manure and paclobutrasol manure test on the growth and yield of rice crops, know the best dose of chicken manure manure on the growth and yield of rice crops, know the influence of paclobutrasol on the growth and yield of rice crops. This study used a complete randomized group design (RAKL) factorial, namely the dose of chicken manure manure and the use of paclobutrasol resulted in 8 kinds of treatment. D0P0: without administration of manure and paclobutrasol, D1: manure manure chicken dose 0,9 kg, D2: manure chicken manure dose 1,8 kg, D3: manure manure chicken dose 2,7 kg, P1: the use of paclobutrasol. Treatment was repeated 4 times so that 32 units of probation were obtained. The experimental unit is a treatment tile consisting of 5 clumps of plants. Observations are observed on the treatment tile. To determine the effect of the treatment of plant extracts, test F is used through variety analysis. As for knowing the significant treatment, used Duncan Test at a rate of 5%. The results showed: (1) The weight of grain perpetak with the treatment without paclobutrasol with a high dose of chicken fertilizer, the result is lower than without the use of manure. While the use of paclobutrasol results is also lower with the dose of manure than without chicken manure, (2) The weight of perpetak grain with paclobutrasol treatment results higher than without the use of paclobutrasol, (3)The dose of chicken manure tends to decrease the yield, both use and without paclobutrasol.